Silver nano particle incorporated Ti metal prepared by chemical treatment for antibacterial and corrosion resistance study. (February 2014) - Rajendran, A.; Vinoth, G.; Shanthi, V.; Barik, R. C.; Pattanayak, D. K.
Abstract : In the present study, attempts are made to incorporate silver nano particles into Ti metal by chemical treatment where first the Ti metals are treated with H2 O2 or NaOH solution separately and then in AgNO3 solution. SEM and TEM results showed that fine nano network structures were uniformly formed by both the H2 O2 and NaOH treatment. Raman result confirmed these networks to be hydrated Ti and sodium hydrogen titanate respectively. Therefore, formed nano network structures were successfully incorporated with silver nano particles of 5–10 nm in size by the subsequent AgNO3 solution. Electrochemical studies showed high corrosion resistance of Ag incorporated Ti metal compared to H2 O2 or NaOH treated Ti metals. Antibacterial study of Ti metal subjected to both H2 O2 –AgNO3 and NaOH–AgNO3 showed zone of inhibition in Staphylococcus aureus compared to only NaOH or H2 O2 or untreated specimens. Steady release of silver ions from thus treated Ti metals into simulated body fluid as measured by AAS coupled with good corrosion resistance property suggests this method to be useful in various biomedical implants.